Failure to thrive: A severe manifestation of interleukin 10 receptor A mutation in adult inflammatory bowel disease. Issue 1 (10th September 2021) - Ruiz, Nicole C.; Kamel, Amir Y.; Liu, Xiuli; Pham, Angela; Forsmark, Christopher; Glover, Sarah
Abstract: Background: Very early‐onset inflammatory bowel disease (VEO‐IBD) secondary to interleukin 10 receptor A ( IL‐10RA ) mutations has aggressive disease courses with increased nutrition needs compared with those in other monogenic forms of IBD. Presentation: A male patient was hospitalized when he was 18 days old for bloody diarrhea, which was diagnosed as Crohn's disease at 6 months old. He showed failure to thrive (FTT) and worsening inflammation while receiving enteral nutrition (EN) and standard IBD treatment. He was hospitalized in 2016, at 28 years old, for a Crohn's flare when sequencing confirmed a heterozygous mutation in IL10‐RA . His weight and plasma micronutrient levels improved when he transitioned to parenteral nutrition (PN). He was initiated on anakinra while awaiting hematopoietic stem cell transplant, with substantial decrease in inflammation. He was able to gain weight, initiate an oral diet, and decrease his PN requirement. Conclusion: Our patient experienced progressive FTT while receiving EN. VEO‐IBD incidence is rising, and its diagnosis is often delayed. Therefore, prompt recognition with treatment initiation is essential to improving nutrition outcomes in this patient population. Further investigation is warranted to determine whether these patients would benefit from early initiation of PN.